Convalescent plasma for COVID‐19: Donor demographic factors associated high neutralising antibody titres. Issue 4 (17th April 2022) - Mehew, Jennifer; Johnson, Rachel; Roberts, David; Griffiths, Alex; Harvala, Heli
Abstract: Background: Convalescent plasma containing high levels of SARS‐CoV‐2 antibodies has been studied as a possible treatment for COVID‐19. Better understanding of predictors of high antibody levels is needed for improving supply of high‐quality therapeutic plasma. Aims: We have evaluated demographic and clinical factors associated with the probability of a convalescent plasma donor having high SARS‐CoV‐2 IgG antibody levels. Methods: A total of 29, 585 convalescent plasma donors employed during the first and second waves of the COVID‐19 pandemic in England were included in this study. All had been tested for SARS‐CoV‐2 IgG antibodies by EUROimmun ELISA. A multivariable logistic regression model was used to quantify the association of the demographic and clinical factors with high (EUROimmun S/Co>6.0) SARS‐CoV‐2 IgG antibody level. Results: Most of the donors were male (23, 024; 78%), with white ethnic background (24, 598;83%) and had not been tested for SARS‐CoV‐2 (15, 266; 52%).Overall, less than 20% of convalescent plasma donors with confirmed or suspected SARS‐CoV‐2 infection harboured high SARS‐CoV‐2 antibody levels ( n = 4, 978). We found that older male donors who had been hospitalised with COVID‐19 were most likely to harbour high levels of antibodies. White donors were less likely to have high SARS‐CoV‐2 antibody levels than donors with Asian orblack ethnic backgrounds residing in affluent areas likely reflecting ethnic inequality previously associated with SARS‐CoV‐2 infection. Discussion: In a time of great uncertainty, and predicted new waves associated with newly emerging SARS‐CoV‐2 variants, these results will help us to target future convalescent plasma collections.